Case report: A case of classic hairy cell leukemia with CNS involvement treated with vemurafenib - Johnson, Anna E.; Raju, Athul Raj; Jacob, Aasems; Hildebrandt, Gerhard C. (Frontiers in Oncology, 2023)
Hairy cell leukemia (HCL) is a rare mature B-cell lymphoproliferative disorder and most often presents as classic hairy cell leukemia. This entity is characterized by indolent course and presence of BRAF V600E mutation. We report the case of an 80-year-old male with history of classical hairy cell leukemia who presented with fatigue, dizziness, shortness of breath, blurring of vision and headache. His initial diagnosis was nine years prior and received treatments with cladribine, pentostatin, and rituximab. Workup showed elevated white blood cell count with atypical lymphocytes, anemia and thrombocytopenia. Peripheral blood smear confirmed HCL relapse and MRI brain showed diffuse non-enhancing masses in the supratentorial and infratentorial regions of the brain. He was initiated on treatment with vemurafenib with improvement in white blood cell count and recovery of platelet count and hemoglobin. Repeat MRI brain after 3 months showed complete resolution of brain lesions. Vemurafenib was discontinued after 6 months with bone marrow biopsy showing no evidence of residual hairy cell leukemia. There has only been limited reports of HCL involvement of central nervous system in the literature. Due to the rarity of the condition, it is not clear which treatments can be effective in intracranial disease control. Our report shows the successful use of vemurafenib resulting in complete remission of relapsed HCL with CNS involvement.